Self-Disclosure of Generation Z - Wibisono, Haekal El Gibrani; Pratisti, Wiwien Dinar (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Purpose: This study aims to explore the self-disclosure of Generation Z with the premise that high interaction with social media will change the way of pouring one's heart from face to face to other social media. Methodology: The descriptive qualitative method was chosen to analyze the data obtained from Generation Z's response to a number of questions that the researchers compiled and distributed in the form of a google form link. Results : Based on the answers from 103 respondents, it is known that Generation Z actually prefers to share their problems through face-to-face rather than through social media with the main reason being that they are afraid of bad things that are not expected before. Meanwhile, close friends or best friends are the first people they choose as a place to share their problems in the real world with the reason that they already have a close and trustworthy relationship. Applications/Originality/Value: The results of this study indicate that Generation Z, which is identical to the generation that is very close to the advancement of information technology, still needs other media that is used to open up or share their problems. They trust their friends or closest people to share their problems, because they still consider the elements of confidentiality and identity.